Smart Horn Control System: A Geo-Fenced, IoT-Based Solution for Noise Pollution Reduction in Sensitive Zones - S Saravanakumar,; S K Pavan Prabhu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Urban noise pollution has emerged as a critical public health issue, particularly near sensitive areas such as schools, hospitals, and old age homes. This research proposes an innovative, technology-driven solution to mitigate unnecessary honking using a smart horn suppression system. By leveraging GPS, Google Maps APIs, IoT-enabled vehicle modules, and geofencing, the system automatically disables or suppresses horn use when a vehicle enters a designated silence zone. The paper presents the design, implementation strategies, system architecture, and a prototype simulation to validate feasibility. Findings show the system's potential to significantly reduce honking-related disturbances, improve public health, and support traffic regulation efforts in urban areas.
Keywords: Horn suppression; geofencing; IoT vehicular system; smart zones; noise pollution control; GPS/Google Maps